2017
DOI: 10.1242/jeb.155242
|View full text |Cite
|
Sign up to set email alerts
|

Ecology of ontogenetic body-mass scaling of gill surface area in a freshwater crustacean

Abstract: Several studies have documented ecological effects on intraspecific and interspecific body-size scaling of metabolic rate. However, little is known about how various ecological factors may affect the scaling of respiratory structures supporting oxygen uptake for metabolism. To our knowledge, our study is the first to provide evidence for ecological effects on the scaling of a respiratory structure among conspecific populations of any animal. We compared the body-mass scaling of gill surface area (SA) among eig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
30
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 22 publications
(30 citation statements)
references
References 79 publications
(115 reference statements)
0
30
0
Order By: Relevance
“…A similar outcome occurred in brown garden snails (Cornu asperum, formerly Helix aspersa), whose growth rate had been increased by artificial selection for increased body size [220]. A natural experiment involving varying natural selection on growth rate in amphipod populations living in springs with versus without visually hunting fish predators also revealed a close match between the ontogenetic scaling of the rates of growth and metabolism [105,136].…”
Section: Resource-demand Modelsmentioning
confidence: 66%
See 4 more Smart Citations
“…A similar outcome occurred in brown garden snails (Cornu asperum, formerly Helix aspersa), whose growth rate had been increased by artificial selection for increased body size [220]. A natural experiment involving varying natural selection on growth rate in amphipod populations living in springs with versus without visually hunting fish predators also revealed a close match between the ontogenetic scaling of the rates of growth and metabolism [105,136].…”
Section: Resource-demand Modelsmentioning
confidence: 66%
“…Several studies in diverse species of plants [193], invertebrates [103,105,136,219,220,222] and vertebrates [218,221,223,224] have shown that increased growth rate is associated with steeper ontogenetic scaling of metabolic rate (slopes often approaching 1) (also see 19,20,98]. This support involves not only numerous correlative analyses, but also multiple experimental manipulations.…”
Section: Resource-demand Modelsmentioning
confidence: 98%
See 3 more Smart Citations